A Developmental and Molecular View of Formation of Auxin-Induced Nodule-Like Structures in Land Plants - Hiltenbrand, Ryan; Thomas, Jacklyn; McCarthy, Hannah; Dykema, Karl J.; Spurr, Ashley; Newhart, Hamilton; Winn, Mary E.; Mukherjee, Arijit (Frontiers in Plant Science, 2016)
Several studies have shown that plant hormones play important roles during legume-rhizobia symbiosis. For instance, auxins induce the formation of nodule-like structures (NLS) on legume roots in the absence of rhizobia. Furthermore, these NLS can be colonized by nitrogen-fixing bacteria, which favor nitrogen fixation compared to regular roots and subsequently increase plant yield. Interestingly, auxin also induces similar NLS in cereal roots. While several genetic studies have identified plant genes controlling NLS formation in legumes, no studies have investigated the genes involved in NLS formation in cereals. In this study, first we established an efficient experimental system to induce NLS in rice roots, using auxin, 2,4-D, consistently at a high frequency (>90%). We were able to induce NLS at a high frequency in Medicago truncatula under similar conditions. NLS were characterized by a broad base, a diffuse meristem, and increased cell differentiation in the vasculature. Interestingly, NLS formation appeared very similar in both rice and Medicago, suggesting a similar developmental program. We show that NLS formation in both rice and Medicago occurs downstream of the Common Symbiotic Pathway. Furthermore, NLS formation occurs downstream of cytokinin-induced step(s). We performed a comprehensive RNA sequencing experiment to identify genes differentially expressed during NLS formation in rice and identified several promising genes for control of NLS based on their biological and molecular functions. We validated the expression patterns of several genes using RT-PCR and show varied expression patterns of these genes during different stages of NLS formation. Finally, we show that NLS induced on rice roots under these conditions can be colonized by nitrogen-fixing bacteria, Azorhizobium caulinodans.